AN ANALYSIS OF PARROT FISH SUPPLY CHAIN IN TOBA SAMOSIR REGENCY - Marisa, Julia; Sitepu, Sukma Aditya (Journal of Community Research and Service, 2019)
Proper supply chain management in tilapia commodities in Toba Samosir Regency is needed to add value, maintain stock and quality, and can be easily reached by consumers/ communities. This study aims to determine the production process, analyze the actors involved, and analyze product flow, money flow and information flow in the tilapia fish supply chain in Toba Samosir Regency. This research is a qualitative descriptive study. Data analysis method is carried out in several steps: 1) Data Collection, 2) Data Reduction, 3) Data Display, 4) Drawing Conclusion and Verification. The results of this study are 1) Tilapia fish production process in Toba SamosirRegency is carried out with two systems, namely the first fish cultivation is done starting from the nursery and the second is cultivation for enlargement. 2) The actors involved in the supply chain system for the freshwater fish industry in Toba Samosir Regency are Fish Cultivators, Collectors, Diluents, Fish Processing Industries, Consumers. 3) There are product flow, money flow and information flow in the supply chain of the freshwater fishing industry in Toba Samosir Regency. Product flow flows from upstream to downstream, financial flow flows from downstream to upstream and information flows flow in both directions.Keywords: Industry; Supply Chain; Tilapia; Toba Samosir Regency.